2019
DOI: 10.1080/02615479.2019.1693533
|View full text |Cite
|
Sign up to set email alerts
|

Navigating relationships in practice learning: voices from practice educators

Abstract: This paper explores the nature and quality of relationships between social work students and their practice educators and discusses how practice educators navigate their multifaceted and complex role in the context of practice learning in England. The data was drawn from individual interviews with 13 practice educators and two focus groups with first year MA social work students. The findings indicate that challenges associated with social differences, in engaging students in learning, and in initiating critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Students wanted to receive timely, quality and critical feedback to help consolidate learning and improve their practice, which was seen as the essence of the supervisory role to lead as a teacher -an idea consistent with Confucian thinking. In this and other studies (Wang et al, 2019;Yeung et al, 2021), students have welcomed critical and constructive feedback to maximise their learning opportunities. Students in this study appreciated the time given by supervisors to prepare and undertake group reflective exercises.…”
Section: Student-focused Approachmentioning
confidence: 93%
“…Students wanted to receive timely, quality and critical feedback to help consolidate learning and improve their practice, which was seen as the essence of the supervisory role to lead as a teacher -an idea consistent with Confucian thinking. In this and other studies (Wang et al, 2019;Yeung et al, 2021), students have welcomed critical and constructive feedback to maximise their learning opportunities. Students in this study appreciated the time given by supervisors to prepare and undertake group reflective exercises.…”
Section: Student-focused Approachmentioning
confidence: 93%
“…Finally, it was identified that it was also beneficial for social work education providers to provide additional support to social work students whilst on placement. In England, established practice is for university tutors to provide structured support to develop placement expectations at the initial meeting and review progress at the interim meeting, supplemented by informal academic and pastoral support as necessary (Williams & Rutter, 2019). There can be an element of perceived separation between academic and practice that results in the 'teaching' of students on placement being considered to be the practice educator's realm.…”
Section: Connectivitymentioning
confidence: 99%
“…Similarly, it was agreed that flexible and responsive approaches and adjustments to other existing procedures were required, including, for example, supervision and direct observations. It was agreed that the traditional face-to-face method was highly beneficial as a means of developing the supervisory relationship within the initial social work student supervision session, offering support, and enabling assessment (Williams and Rutter, 2019). However, it was also recognised that other forms could provide equally effective supervision.…”
Section: Flexible and Creative Solutionsmentioning
confidence: 99%
See 1 more Smart Citation